2022
DOI: 10.1002/dad2.12347
|View full text |Cite
|
Sign up to set email alerts
|

No difference in retinal fluorescence after oral curcumin intake in amyloid‐proven AD cases compared to controls

Abstract: Introduction Previous work has showed the in vivo presence of retinal amyloid in Alzheimer's disease (AD) patients using curcumin. We aimed to replicate these findings in an amyloid biomarker–confirmed cohort. Methods Twenty‐six patients with AD (age 66 [+9], Mini‐Mental Status Examination [MMSE] ≥17) and 14 controls (age 71 [+12]) used one of three curcumin formulations: Longvida, Theracurmin, and Novasol. Plasma levels were determined and pre‐ and post‐curcumin retina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…Methodological differences in curcumin protocols and quantification may explain the varied findings (Table 1). Ngolab et al (29) theorized that the higher RAC they found compared with Koronyo et al may have been due to higher curcumin dosing over a shorter period, whereas results from den Haan et al (31) suggest that curcumin uptake may vary. In addition, the retina's inherent autofluorescence may mask the curcumin signal.…”
Section: In Vivo Detection Of Aβ Plaques In Human Retinasmentioning
confidence: 94%
See 1 more Smart Citation
“…Methodological differences in curcumin protocols and quantification may explain the varied findings (Table 1). Ngolab et al (29) theorized that the higher RAC they found compared with Koronyo et al may have been due to higher curcumin dosing over a shorter period, whereas results from den Haan et al (31) suggest that curcumin uptake may vary. In addition, the retina's inherent autofluorescence may mask the curcumin signal.…”
Section: In Vivo Detection Of Aβ Plaques In Human Retinasmentioning
confidence: 94%
“…Although the abovementioned studies strongly suggest the presence of retinal Aβ in AD and associations between retinal Aβ and cognition and/or AD pathology in the brain, den Haan et al (31) found no differences in retinal fluorescent signals between patients with biomarker positive AD and NCs using 3 formulations of oral curcumin. In participants who received the standard formulation (Longvida, Verdure Sciences, Noblesville, IN), quantitative assessment revealed no difference in hyperfluorescence between biomarker-positive AD participants and NCs.…”
Section: In Vivo Detection Of Aβ Plaques In Human Retinasmentioning
confidence: 99%
“…The cost-effective and non-invasive detection of retinal amyloid burden carries the potential for early AD identification and monitoring (2, 3840). Thus, several retinal amyloid imaging methodologies have recently been developed (41, 42), such as scanning laser ophthalmoscopy (SLO) (17, 39, 4246) and hyperspectral retinal imaging (13, 3941). SLO imaging offers the opportunity to visualize and quantify not only the Aβ plaques (AP), but also the retinal arteries and veins (17, 44, 45, 47).…”
Section: Introductionmentioning
confidence: 99%
“…The cost-effective and non-invasive detection of retinal amyloid burden carries the potential for early AD identification and monitoring [ 2 , 38 40 ]. Thus, several retinal amyloid imaging methodologies have been recently developed [ 41 , 42 ], including scanning laser ophthalmoscopy (SLO) [ 17 , 39 , 42 46 ] and hyperspectral retinal imaging [ 13 , 39 41 ]. SLO fluorescence imaging following curcumin administration provides an opportunity to visualize and quantify not only the Aβ plaques (AP) but also the retinal arteries and veins [ 17 , 44 , 45 , 47 ].…”
Section: Introductionmentioning
confidence: 99%